The pedagogy of shame. Education in the face of the demokratur of ignoramuses - Kobylarek, Aleksander (Journal of Education Culture and Society, 2020)
This article relates to the slogan of one of the populist political parties in Poland – “the pedagogy of shame”. It is an example of manipulation and the creation of simulacra in social life in order to justify the necessity of assuming power. On accomplishing this,  the slogan becomes the primary principle in the management and rearing of a new society fed on illusions. The author points to the deeper roots of a pathologies which define corrupt power – indifference or acceptance of minor injustices, lack of civic engagement, insouciance with regard to the natural and social environments, the creation of unhealthy arrangements and relationships in small social groups and institutions, including educational – from the lowest level up to the university. In conclusion, the author indicates the necessity of supporting the development of civic society as understood by M. Gruntvig.